Antifungal Activity of Compounds obtained from Sawdust and Stem Bark of Sasswood Tree (Erythrophleum suaveolens) on Wood Rot Fungi - D.O. Ekhuemelo; F.S. Agbidye; J.V. Anyam; C. Ekhuemelo; J.O. Igoli (Journal of Applied Sciences and Environmental Management, 2019)
Extracts and compounds from the sawdust and stem bark of Erythrophleum suaveolens were studied for antifungal activity. The plant materials were extracted using hexane, ethyl acetate and methanol to obtain the crude extracts. Column chromatography over silica gel was used to purify the extracts and obtain pure compounds. Betulin and 21- acetoxylupenone were obtained from the stem bark and cycloeucalenol from the sawdust. The compounds were very active on most of the fungi with zones of inhibition between 18 to 23 mm. Minimum Inhibition Concentration (MIC) was highest at 50 µg/mL against Aspergillus fumigatus, Coniophora puteana, Fibroporia vaillantii, Fomitopsis pinicoca, Gloeophyllum sepiarium, Phaeolus schweinitzii and Rhizopus spp. whereas antifungal activity was least at MFC of 200 µg/mL. The study demonstrated that E. suaveolens stem bark and sawdust isolates possess antifungal activity and could be used in the control of the soft-rot, brown-rot, wet rot and white-rot of wood and diseases caused by wood fungi.